Comparison of Vitamin E in Combination with Mafenamic Acid Versus Mafenamic Acid Alone for Management of Primary Dysmenorrhea - Kanwal, Rabia; Pervaiz, Mahwish; Saeed, Qiarush; Munir, Muhammad Shahbaz (Indus Journal of Bioscience Research, 2025)
Introduction: Painful menstrual cramps, known as primary dysmenorrhea, are a common gynecological condition that affects a great number of women across the globe. Current treatments may include use of a non steroidal anti inflammatory drugs (NSAIDS) as mafenamic acid. Recent research indicated the interaction of vitamin E with NSAIDs may intensify pain relief. Methodology: The core objective of the study was to compare the efficacy of vitamin E combined with mafenamic acid versus mafenamic acid alone for the management of primary dysmenorrhea was evaluated in randomized controlled trial. Sixty-six participants were randomly divided into two groups. Before and after treatment, pain intensity was assessed by means of the Visual Analogue Scale (VAS). Results: The reduction of pain scores in both groups was found to be significant. While combining vitamin E with mafenamic acid showed highest decrease in VAS score after tuberculosis treatment compared to mafenamic acid alone, these results were interpreted with caution. Demographic and clinical variables were similar between balanced groups. Conclusion: The addition of vitamin E to mafenamic acid may be of advantage in relieving the pain of primary dysmenorrhea rather than the use of mafenamic acid alone. These results supported previous findings, suggested that the combination of antioxidants with NSAIDs for the management of menstrual pain can be beneficial for such type of disorders.